Предмет: Математика, автор: zhangaiev20

Помогите!!!!! Очень нужно пожалуйста

Приложения:

Ответы

Автор ответа: Matematiktm
1

Ответ:

Пошаговое объяснение:

y=ln(x^{2} +5);\\y^{'} =(ln(x^{2} +5))^{'}=\frac{(x^{2} +5)^{'}}{x^{2} +5} =\frac{2x}{x^{2} +5} \\y^{''}=(\frac{2x}{x^{2} +5})^{'}=2\frac{(x)^{'}(x^{2} +5)-(x^{2} +5)^{'}x}{(x^{2} +5)^{2} } =2\frac{x^{2} +5-2x^{2} }{(x^{2} +5)^{2} }=\frac{10-2x^{2} }{(x^{2} +5)^{2} }

y^{''}=\frac{d^{2}y}{d x^{2}}= \frac{10-2x^{2} }{(x^{2} +5)^{2} }

Похожие вопросы